A Physiological Assessment Of Pranayama's Impact On Autonomic Nervous System Regulation - Dr. Laxmikanta Rana (Revista Electronica de Veterinaria, 2024)
The ancient breathing techniques from yoga known as pranayamas are believed to promote meditative states, lower stress levels, and expand lung capacity. It is still necessary to identify the physiological processes by which these behaviours alter the human neurological system. Reviewing research on the effects of breathing exercises on the human brain and mind was the goal of this project. We looked at English-language articles that were published between 2010 and 2024. The PRISMA guidelines served as the foundation for the inclusion and exclusion criteria used to screen publications from the Science Direct, PubMed, and Virtual Health Library databases. In addition, the Prospective Register of Systematic Reviews registration and the patient/population, intervention, comparison, and outcome techniques were taken into consideration. Fourteen out of the fifty articles met the requirements. They were compared critically to one another and shown in a table with the following columns: study, nation, sample size, age, gender, goal, method, and result. The evaluated studies demonstrated a slight but constant shift in Autonomic nervous system (ANS) metrics towards parasympathetic dominance, an increase in paroxysmal gamma waves, changes in wave power and expression in EEG reading, and improved accuracy and focus in cognitive tests. The 14 publications together emphasise the effects of yoga breathing methods on emotional and cognitive functioning. Consequently, in order to effectively substantiate these results, more extensive, well planned, randomised studies of pranayama on a variety of systems must be conducted.